Partai Politik, Kepala Daerah Dan Performa Ekonomi Regional (Studi Kasus Provinsi di Indonesia Tahun 2010-2014) - Sulistiyana, Rudy Prasetyawan; Samudro, Bhimo Rizky; Pratama, Yogi Pasca (Jurnal Ilmu Ekonomi dan Pembangunan, 2015)
This study aims to determine the effect of governor selected as result elections to regional economic performance and see comparison economic performance of political parties within the scope of regional (province) toward economic performance of political parties within the scope of national in entire of Indonesia.The analytical method used in this research were quantitative method with a comparative analysis of average with statistical inference be paired sample t-test and economic performance index. Variables used in this research were economic growth, inflation, unemployment rate, unemployment, poverty, poverty level, inequality, regional head and dominance political parties in a province. Population of study includes 33 provinces in Indonesia from 2010-2014.The results of this study are : 1) there is no difference in the performance of regional head incumbent and non-incumbent from perspective of economic performance and 2) performance of political parties at the provincial level from 2010-2014 has not been satisfactory in building a welfare society in the field of economy through policy making. Keyword  :       Regional Head Incumbent, Regional Head Non-Incumbent, Political Parties, Economic Performance Index, Paired Sample T-TestJEL Classification: O18, P47